The mediating effects of professional development on the relationship between teacher competence and teaching quality in Oman - Shakar Al Balushi , Sara Bereh; Supian , Kamisah; Sivachandran (International Journal of Accounting, Finance and Business, 2025)
This research explored professional development as a mediating role to influence the teaching quality in Oman’s primary schools by focusing on teacher competence, which is again focused on teaching enthusiasm and teacher self-efficacy. Primary and secondary data were used for this study. The primary data was collected through questionnaires and interviews. The sample size of the study is 250 and the teachers working in various schools are the participants for this reserch. The key points indicate that teacher competence is important, because it shapes the outcomes of the classroom, teaching enthusiasm to develop a higher quality teaching, and the confidence and ability of the teachers to handle the classroom efficiently. The study highlighted that the teachers who are engaged with higher and continuous professional development programs have higher levels of the latest teaching skills and strategies, which contributes to providing better student learning and improving teaching quality by the influence of teacher competence. The self-efficacy of teachers is important in terms of predicting student engagement. In terms of shaping the self-efficacy of teachers, there is an important role for initial teacher training because it provides the foundational skills and knowledge which is essential towards effective classroom practice. Moreover, the teachers express their enthusiasm in terms of their learning process and subjective matter as part of teaching, which supports to impact on the value they place on the subject and students' expectations in terms of their ability to succeed. Professional development involves learning opportunities like peer collaboration, mentoring, workshops, and training sessions. Furthermore, professional learning communities, reflective practices, and coaching are valuable in terms of enhancing the experiment of teachers and support to adapt and refine strategies in terms of meeting the learner's diverse needs.